Measurement And Characterization of Radio Propagation Channels from The Patient Room Hub to The Nurse Station Server for WBAN Medical Applications - Mauludiyanto, Achmad; Hendrantoro, Gamantyo; Krisdaniawan, Darien Raditya (Department of Electrical Engineering ITS and FORTEI, 2022)
As time passes, technology is demanded to be more sophisticated, efficient, and fully automatic. Technology development also impacts the medical field since hospitals require a tool that can automatically, thoroughly, and accurately record the physical condition of patients in the inpatient room and forward the results to be checked by the nurses on duty at the nurse station. Automation of patient data recording needs to be performed flexibly and comfortably for patients; thus, a wireless device channelling sensors on the patient's body to the nurse station is required. On this account, it demands a measurement to characterise the radio propagation channels. Therefore, this paper highlights the radio channel between the inpatient room hubs and the nurse station server. The measurement was performed in two rooms separated by a wall in the Antenna and Propagation Laboratory, representing an inpatient room and the nurse station. Further, the channel frequency was set at 3 GHz with a bandwidth of 200 MHz. Through the Vector Network Analyzer (VNA), the result revealed the channel response characteristic that the denser the propagation channels, the lower the power received and vice versa.